A cross-cultural study of request speech act: Iraqi and Malay students - Abdul Sattar, Hiba Qusay; Farnia, Maryam (University of Isfahan, 2014)
Several studies have indicated that the range and linguistics expressions of external modifiers available in one language differ from those available in another language. The present study aims to investigate the cross-cultural differences and similarities with regards to the realization of request external modifications. To this end, 30 Iraqi and 30 Malay university students are selected as the participants of this study. Spencer-Oatey's (2008) rapport management theoretical framework is used to examine how face rapport is managed through the use of external modifications. The corpus consists of responses to a Discourse Completion Test (DCT) consisting of eight situations. The questionnaires, adopted from Rose (1994), were distributed among Iraqi students and Malaysian Malay students studying at Universiti Sains Malaysia, Malaysia. The corpus was then analyzed based on Blum-Kulka, House and Kasper’s (1989) classification of external modifiers. The primary objective of this paper is to compare the effect of situational factors on the realization patterns of request modification between Iraqi and Malay university students .The findings indicated that grounders are the most common external modifier used by the subjects. Results also show more similarities than differences between the subjects under study in terms of the use of mitigation devices such as apologies, compliments and gratitude. However, both Iraqis and Malays differ in their perception of the situational factors. Finally, the study suggests some pedagogical implications for both ESL and EFL teachers.